Design and Implementation of a Remote Control Based Home Automation System - Najeem Olawale Adelakun; Samuel Adeniyi Omolola (LPPM Universitas Andalas, 2024)
This study describes an innovative remote control-based home automation system that uses electronic components such as IC TSOP1738, BC 548, IC CD4017, capacitors, diodes IN4007, resistors, and LEDs to boost household convenience. The essential component, TSOP1738, acts as an infrared receiver, decoding signals from a typical remote control and enabling continuous communication inside the system. The BC 548 transistor acts as a critical switch, regulating current flow to connected appliances. The IC CD4017 enables sequential operation for a more systematic approach to device control. Meticulously constructed circuitry, including capacitors, diodes IN4007, and resistors, ensures optimal performance and stability. LEDs serve as intuitive indicators, offering visual feedback on device status. Extensive testing validates the system's robustness, precision, and dependability. The study investigates real applications that demonstrate the system's adaptability in various household situations, thereby contributing to the progress of home automation technology. This study provides an accessible and efficient solution for modern families, with potential developments in the future to increase automation capabilities and usage on a larger scale.